ANALISIS KONSUMSI BAHAN BAKAR ETANOL-PREMIUM PADA MESIN EMPAT TAK - Sahional Ishak; Wawan Rauf (Asosiasi Dosen Muda Indonesia, 2024)
Fuel needs in Indonesia are generally met by fossil energy sources such as Pertamax, Pertalite, Premium, Super TT and Solar which are non-renewable. Apart from that, in line with the increase in the volume of motorized vehicles, this has an impact on increasing the amount of fuel used so it is feared that the availability of fossil energy will soon run out. Therefore, saving fuel consumption is a must to maintain its availability. Bioethanol is an alternative fuel that has not been widely used as a substitute or additive for fossil fuels, because it is still in the research and testing stage. Overall, the use of bioethanol has many advantages whether used as a mixed or pure fuel. This research aims to test the use of ethanol and premium mixed fuels with various blend percentages. Consumption of premium mixed fuel and ethanol compared to pure premium fuel consumption. The test motorbike used was a 4 stroke engine with a cylinder volume of 108 cc. The percentage of premium and ethanol mixture was varied respectively, 75% premium and 25% ethanol (P75+E25), 50% premium and 50% ethanol (P50+E50%), and 25% premium and 75% ethanol (P25+E75). The engine rotation speed was varied respectively 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm and 5000 rpm. The research results show that for all types of fuel, there is an increase in fuel consumption along with increasing engine speed. The lowest average fuel consumption was obtained with a mixture of 75% premium fuel and 25% ethanol (P75+E25). The percentage reduction in consumption was 13.8% compared to pure premium consumption. The highest average fuel consumption was obtained with a mixture of 25% premium and 75% ethanol compared to all types of fuel.